2021
DOI: 10.1038/s41467-021-25855-2
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient intercellular spreading of protein misfolding mediated by viral ligand-receptor interactions

Abstract: Protein aggregates associated with neurodegenerative diseases have the ability to transmit to unaffected cells, thereby templating their own aberrant conformation onto soluble homotypic proteins. Proteopathic seeds can be released into the extracellular space, secreted in association with extracellular vesicles (EV) or exchanged by direct cell-to-cell contact. The extent to which each of these pathways contribute to the prion-like spreading of protein misfolding is unclear. Exchange of cellular cargo by both d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 91 publications
2
68
0
1
Order By: Relevance
“…Subsequently, infections were also performed with 22L, as this strain resulted in high infection rates and could be propagated reliably in cell culture [ 38 , 39 ]. More recently, neuronal and astroglial cultures from wildtype or transgenic mice have also been successfully used for infection studies [ 41 , 68 , 84 , 85 ]. Because of the lack of species-specific cell culture systems, researchers focused on ectopic expression of species-specific PrP C in heterologous cell cultures.…”
Section: Cellular Models For Prion Propagationmentioning
confidence: 99%
“…Subsequently, infections were also performed with 22L, as this strain resulted in high infection rates and could be propagated reliably in cell culture [ 38 , 39 ]. More recently, neuronal and astroglial cultures from wildtype or transgenic mice have also been successfully used for infection studies [ 41 , 68 , 84 , 85 ]. Because of the lack of species-specific cell culture systems, researchers focused on ectopic expression of species-specific PrP C in heterologous cell cultures.…”
Section: Cellular Models For Prion Propagationmentioning
confidence: 99%
“…The same mechanism is described for HSV-1, which catalyzes the aggregation of amyloid-β in vitro and in vivo and is a well-established risk factor for AD [ 76 , 78 ]. Recently, it was demonstrated that viral particles (including SARS-CoV-2 spike protein) facilitate the spreading of proteopathic seeds by altering intercellular cargo transfer [ 79 ].…”
Section: Chaptermentioning
confidence: 99%
“…Whether and in what way these findings might contribute to the development of PD is unknown. Furthermore, SARS-CoV-2 has been shown to also influence other proteins involved in neurodegenerative diseases such as AD: the expression of SARS-CoV-2 spike protein S has been linked to an increased spreading of Tau and cytosolic prions in-vitro and further prompted the aggregation of these proteins (Liu et al 2021 ). A shift in localization of Tau from axons to the soma and hyperphosphorylation of Tau, both hallmarks of early stages of tauopathy, have been observed in SARS-CoV-2-infected neurons, resulting in cell death in 3D human brain organoids (Ramani et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%